2022
DOI: 10.1186/s12974-022-02521-y
|View full text |Cite
|
Sign up to set email alerts
|

Far infrared light irradiation enhances Aβ clearance via increased exocytotic microglial ATP and ameliorates cognitive deficit in Alzheimer’s disease-like mice

Abstract: Background Exposure to sunlight may decrease the risk of developing Alzheimer’s disease (AD), and visible and near infrared light have been proposed as a possible therapeutic strategy for AD. Here, we investigated the effects of the visible, near infrared and far infrared (FIR) light on the cognitive ability of AD mice, and found that FIR light also showed potential in the improvement of cognitive dysfunction in AD. However, the related mechanism remains to be elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 81 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…As AD progresses, microglial cells experience an age-related reduction in microglial capacity to interact with Aβ 46 . With aging, activated microglial cells ineffectively eliminate Aβ and the release of proinflammatory cytokines is elevated 47 .…”
Section: Discussionmentioning
confidence: 99%
“…As AD progresses, microglial cells experience an age-related reduction in microglial capacity to interact with Aβ 46 . With aging, activated microglial cells ineffectively eliminate Aβ and the release of proinflammatory cytokines is elevated 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial or intranasal PBM for brain stimulation with R and NIR light has focused attention on positive outcomes on cognitive functions, the repair of neurodegenerative processes, control of energy metabolism, and adjustment of chronic brain inflammatory processes in AD subjects. Publications of experimental and clinical studies on tPBM in AD and other neurodegenerative disorders and ischemic brain injuries have demonstrated that this modality of therapy stimulates metabolic processes in brain tissue, increases intracellular ATP production and revives neuronal mitochondrial activity; modulates local oxidative stress; favors angiogenesis, capillary and lymphatic revascularization; restores destroyed synapses and generates new synapses; revitalizes the growth of new neural cells and acts as a neuroprotector, thus improving cognitive function and memory [ 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 ].…”
Section: Photobiomodulation Of the Brain And The Treatment Of Alzheim...mentioning
confidence: 99%
“…Similarly, photobiomodulation employing visible red light (670 nm), non-visible near infrared (NIR, 800–1090 nm), and even far infrared (FIR, 3–25 µm) show encouraging results in the attenuation of symptoms associated with dementia including a reduction in Aβ deposition, size and number of plaque and fibril formation, clearance of misfolded proteins, increased ATP production and reduced ROS production, improved executive and cognitive functions, processing speed, memory performance, mood, energy, and sleep [ 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 ] ( Table 1 ). The proposal that red and near-infrared wavelengths may promote melatonin synthesis in mitochondria via the pathway involving nitric oxide and enhanced activity of soluble adenylyl cyclase further bolsters the synergistic relationship between light and melatonin [ 218 , 219 ].…”
Section: Aberrant Phase Separation Is the Fundamental Molecular Drive...mentioning
confidence: 99%
“…The ability to increase adenosine triphosphate (ATP) production in mitochondria is one of the most widely accepted mechanisms behind the effectiveness of photobiomodulation in dementia and other health challenges [ 211 , 217 , 220 , 221 , 222 ]. The fact that both infrared light and melatonin increase ATP production, and the adenosine moiety of ATP which is structurally similar to melatonin is capable of solubilizing protein aggregation point to the existence of a most unexpected, dynamic relationship between NIR light and melatonin that is inextricably connected to the regulation of hydrogen bonds, viscosity, protein hydration, and protein aggregation ( Figure 1 ).…”
Section: Aberrant Phase Separation Is the Fundamental Molecular Drive...mentioning
confidence: 99%